Results on Random Differential Inclusions (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Here, we investigate the boundary value problem for fourth order of randomdifferential inclusions and proved the existence result of random solution through Krasnosel'skiifixed point result.